Face2face. Elementary: Student's Book - Redston C. Chris (Cambridge, Cambridge University Press, 2008)
Face2face is a general English course for adults and young adults who want to learn to communicate quickly and effectively in today's world. Based on the communicative approach, it combines the best in current methodology with special new features designed to make learning and teaching easier. Vocabulary and grammar are given equal importance and there is a strong focus on listening and speaking in social situations. Face2face is fully compatible with The Common European Framework of Reference for Languages and gives students regular opportunities to evaluate their progress. Face2face Elementary reviews A1 and takes students to the end of A2. The Student's Book provides approximately 80 hours of core teaching material, which can be extended to 120 hours with the inclusion of the photocopiable resources and extra ideas in the Teacher's Book. Each self-contained double-page lesson is easily teachable off the page with minimal preparation.